2018
DOI: 10.3233/jad-170740
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution, Asymmetry, and Clinical Correlates of Tau Uptake on [18F]AV-1451 PET in Atypical Alzheimer’s Disease

Abstract: Background: Despite common pathology, Alzheimer’s disease (AD) can have multiple clinical presentations which pathological studies suggest result from differences in the regional distribution of tau pathology. Positron emission tomography (PET) ligands are now available that can detect tau proteins in vivo and hence can be used to investigate the biological mechanisms underlying atypical AD. Objective: To assess regional patterns of tau uptake on PET imaging in two atypical AD variants, posterior cortical at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 56 publications
7
63
0
Order By: Relevance
“…Interestingly, SCCA performed on tau-PET and MRI-volumes and on tau-PET and FDG-PET uptakes selected mostly bilateral or right regions in the first canonical dimension and mostly left regions in the second canonical dimension. This likely reflects the fact that tau uptake and neurodegeneration in atypical AD subjects can be asymmetric (Tetzloff et al, 2018). In contrast, tau deposition was only mildly related to the degeneration of white matter tracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, SCCA performed on tau-PET and MRI-volumes and on tau-PET and FDG-PET uptakes selected mostly bilateral or right regions in the first canonical dimension and mostly left regions in the second canonical dimension. This likely reflects the fact that tau uptake and neurodegeneration in atypical AD subjects can be asymmetric (Tetzloff et al, 2018). In contrast, tau deposition was only mildly related to the degeneration of white matter tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, 31 also underwent FDG-PET. All patients underwent a comprehensive neurological evaluation by a Behavioral Neurologist (KAJ or JGR), details of which can be found in a previous study (Tetzloff et al, 2018). The demographic and clinical features of the cohort are shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the asymmetrical cerebral involvement in AD is considered to be nondirectional, or as Derflinger and colleagues describe it, "asymmetric but not lateralized" [4,5]. However, a number of studies have reported consistent left-lateralized damage in AD, particularly to the hippocampus and white matter integrity [10][11][12][13][14], and also in terms of amyloid and tau pathology [6,15]. Furthermore, the degree of leftward cerebral asymmetry has been associated with disease progression and progressively declining cognitive performance [6,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Considering atypical manifestations of AD, those with posterior cortical atrophy display more cortical uptake in occipital areas relative to logopenic progressive aphasia (lvPPA) patients, whilst lvPPA is characterised by more temporal and frontal uptake(Tetzloff et al, 2018). Despite having a favourable pharmacokinetic profile and specificity for tau, further study is required in determining the clinical utility of in vivo imaging using [ 18 F]AV-1451 in AD and MCI(Chien et al, 2014;Zhang et al, 2012).…”
mentioning
confidence: 99%